Construction and phenotypic characterization of Mycobacterium smegmatis mutants deficient in the MutY DNA glycosylase - Hassim, Farzanah (My University, 2014)
Mycobacterium tuberculosis is a facultative pathogen that causes tuberculosis and it accounted for 1.4 million deaths worldwide in 2011. During infection reactive species are released by macrophages as part of the hosts‟ immune response, causing damage to the pathogen‟s DNA. Since mycobacterial genomes are G+C rich the guanine base is more susceptible to oxidative damage which results in the formation of 7,8-dihydro-8-oxoguanine (8-oxoG) lesions which are subsequently repaired by the Fpg/Nei family of DNA glycosylases of the base excision repair (BER) pathway. Mycobacteria possess four copies of the Fpg/Nei glycosylases with the Fpg homologue displaying an overlapping role with MutM in the GO system. Loss of the Fpg/Nei DNA glycosylases leads to mispaired bases during replication which are subsequently repaired by the MutY DNA glycosylase. Previously, in our laboratory we showed that a deficiency of two Fpg/Nei glycosylases displayed no differences in survival of M. smegmatis mutants under oxidative stress and a 2-3 log difference was observed only when three or all four of the DNA glycosylases were inactivated. Surprisingly, there was no corresponding increase in mutator phenotype for all the combinatorial Fpg/Nei deficient mutants compared to the parental strain. A recent study further showed that a deficiency in M. smegmatis MutY glycosylase also displayed no notable susceptibility to oxidative stress or increase in mutagenesis. Since in E.coli a double mutM and mutY mutant displayed an increased mutator phenotype compared to the individual mutants, it was plausible to investigate the role of MutY in combination with the Fpg/Nei family of DNA glycosylases in mycobacteria to understand whether these DNA glycosylases display overlapping and/or compensatory functions in dealing with oxidative damage. Using homologous recombination the mutY gene was deleted in the parental and in the Fpg/Nei deficient mutant strains. Deletion of mutY together with the Fpg/Nei family of DNA glycosylasesdisplayed similar in vitro growth kinetics as the parental strain under normal culture conditions. However, under in vitro oxidative stress conditions the mutY deficiency especially in the absence of all four Fpg/Nei DNA glycosylases results in a greater reduction in survival of the mutants with a general increase in mutation rates. Consistent with these data was the significant increase in C → A and A → C mutations with the progressive loss of the DNA glycosylases as assessed by the spectral analysis of rifampicin resistant mutants. Taken together these data indicate that the mycobacterial MutY DNA glycosylase has antimutator properties and possibly has a more significant role in mycobacterial genome maintenance compared to the Fpg/Nei family of DNA glycosylases.
Keywords: Mycobacterium